2021
DOI: 10.1002/ardp.202100160
|View full text |Cite
|
Sign up to set email alerts
|

Binding of boswellic acids to functional proteins of the SARS‐CoV‐2 virus: Bioinformatic studies

Abstract: Boswellic acids (BAs) have been shown to possess antiviral activity. Using bioinformatic methods, it was tested whether or not acetyl‐11‐keto‐β‐boswellic acid (AKBA), 11‐keto‐β‐boswellic acid (KBA), β‐boswellic acid (BBA), and the phosphorylated active metabolite of Remdesivir® (RGS‐P3) bind to functional proteins of SARS‐CoV‐2, that is, the replicase polyprotein P0DTD1, the spike glycoprotein P0DTC2, and the nucleoprotein P0DTC9. Using P0DTD1, AKBA and KBA showed micromolar binding affinity to the RNA‐depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…These compounds bind at the H1-H2 binding pocket Ahmad et al ( 2021 ) Natural antioxidants including glycyrrhizin and its metabolite 18-glycyrrhetinic acid Molecular docking, and MD simulations Glycyrrhizin was found as the best ligand showing strong inhibition of five SARS-CoV-2 proteins Glycyrrhizin and its metabolite 18-glycyrrhetinic acid have shown a strong binding affinity for MPro, helicase, RdRp, spike, and E-channel proteins, while a flavonoid Baicalin also strongly binds against PLpro and RdRp Rehman et al ( 2021 ) 56 licorice compounds Silico interaction of main licorice components against SARS-CoV-2 infection Glycyrrhizic acid, considered as a licorice major active ingredient, have a significant antiviral effects Glycyrrhizic acid have the highest affinity to all targets Maddah et al ( 2021 ) β-Boswellic acid and glycyrrhizic acid comparing with many compounds Molecular docking studies to identify binding of medicinal metabolites with SARS-CoV-2 E protein Out of screened compounds, β-boswellic acid (B. serrata) was found to be most suitable, along with glycyrrhizic acid (G. glabra) antiviral activities against enveloped viruses They are strong SARS-CoV-2 E protein inhibitors Fatima et al ( 2022 ) Bioactive compounds from Boswellia serrata Computational method. AutoDock and PATCHDOCK It was found that Euphane possesses most significant inhibitory potential against all of four receptors of virus The top five ligands, bioactive compounds, bind to the catalytic dyad amino acid residues of Mpro by different bonding interactions Roy and Menon ( 2022 ) Acetyl‐11‐keto‐β‐boswellic acid (AKBA), 11‐keto‐β‐boswellic acid (KBA), and β‐boswellic acid (BBA) Molecular modeling and bioinformatics BAs have been reported to possess antiviral properties as antiviral drugs The data of this bioinformatics study suggest that BAs target SARS‐CoV‐2 viruses on an atomic scale on three functional proteins, which in turn are responsible for human cell adhesion or viral RNA replication Caliebe et al ( 2021 ) Alpha-boswellic acid (ABA) and beta-boswellic acid (BBA) which are active components Docking st...…”
Section: Resultsmentioning
confidence: 89%
“…These compounds bind at the H1-H2 binding pocket Ahmad et al ( 2021 ) Natural antioxidants including glycyrrhizin and its metabolite 18-glycyrrhetinic acid Molecular docking, and MD simulations Glycyrrhizin was found as the best ligand showing strong inhibition of five SARS-CoV-2 proteins Glycyrrhizin and its metabolite 18-glycyrrhetinic acid have shown a strong binding affinity for MPro, helicase, RdRp, spike, and E-channel proteins, while a flavonoid Baicalin also strongly binds against PLpro and RdRp Rehman et al ( 2021 ) 56 licorice compounds Silico interaction of main licorice components against SARS-CoV-2 infection Glycyrrhizic acid, considered as a licorice major active ingredient, have a significant antiviral effects Glycyrrhizic acid have the highest affinity to all targets Maddah et al ( 2021 ) β-Boswellic acid and glycyrrhizic acid comparing with many compounds Molecular docking studies to identify binding of medicinal metabolites with SARS-CoV-2 E protein Out of screened compounds, β-boswellic acid (B. serrata) was found to be most suitable, along with glycyrrhizic acid (G. glabra) antiviral activities against enveloped viruses They are strong SARS-CoV-2 E protein inhibitors Fatima et al ( 2022 ) Bioactive compounds from Boswellia serrata Computational method. AutoDock and PATCHDOCK It was found that Euphane possesses most significant inhibitory potential against all of four receptors of virus The top five ligands, bioactive compounds, bind to the catalytic dyad amino acid residues of Mpro by different bonding interactions Roy and Menon ( 2022 ) Acetyl‐11‐keto‐β‐boswellic acid (AKBA), 11‐keto‐β‐boswellic acid (KBA), and β‐boswellic acid (BBA) Molecular modeling and bioinformatics BAs have been reported to possess antiviral properties as antiviral drugs The data of this bioinformatics study suggest that BAs target SARS‐CoV‐2 viruses on an atomic scale on three functional proteins, which in turn are responsible for human cell adhesion or viral RNA replication Caliebe et al ( 2021 ) Alpha-boswellic acid (ABA) and beta-boswellic acid (BBA) which are active components Docking st...…”
Section: Resultsmentioning
confidence: 89%
“…In another study, using the computational method, 26 bioactive compounds from Boswellia serrata showed activity against SARS-CoV-2 (Roy and Menon 2021 ). Furthermore, in bioinformatic studies, BA shows high affinity for binding to three functional proteins of SARS-CoV-2 responsible for adhesion and virus replication, as do antiviral agents (Caliebe et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Li et al ( 2021 ) provided experimental evidence showing that glycyrrhizin inhibits SARS-CoV-2 infection through interaction with high-affinity S protein and prevents binding of recombinant S protein to host cells. Also, boswellic acid has been shown to have a high affinity for binding the functional S protein of SARS-CoV-2 ( Caliebe et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The candidate drugs were able to cause a great inhibitory effect on SARS-CoV-2 and also reduce the burden of in vitro and clinical experiments (Heiat et al 2021 ). The in silico study of Kadhim et al involved an evaluation on the inhibitory effects of boswellic acid and beta-boswellic acid against SARS-CoV-2 virus (Kadhim et al 2021 ; Caliebe et al 2021 ). Considering how the reproduction of this virus depends on the binding of its spikes to the cell receptors, the docking studies of this survey were conducted using Molecular Graphic Laboratory (MGL) tools and AutoDock Vina application to gather data on the interaction of virus spikes and alpha-Boswellic acid or beta-Boswellic acid, which resulted in indicating the existing of a high affinity among them and also confirmed the safety of using large doses of these compounds in humans due to their LC50 values (Kadhim et al 2021 ).…”
Section: Sars-cov-2mentioning
confidence: 99%